Development of Pedagogic Competencies of PGMI Teachers in Improving the Quality of Learning in Islamic Elementary Schools - Siddik Romadhan (LP2M IAI Al-Khairat Pamekasan, 2026)
This study examines the development of pedagogical competence of PGMI teachers in improving the quality of learning in Islamic Elementary Schools. Pedagogical competence is a crucial aspect that determines the effectiveness of teaching and learning processes, particularly in integrating academic content with Islamic values. This research aims to analyze how the development of teachers’ pedagogical competence contributes to enhancing learning quality. The study employs a qualitative approach with a descriptive design. Data were collected through in-depth interviews, classroom observations, and documentation, and analyzed using an interactive model involving data reduction, data display, and conclusion drawing. The findings indicate that the development of pedagogical competence significantly improves teachers’ ability to design systematic and student-centered learning, implement innovative teaching methods, and conduct comprehensive evaluations. It also enhances students’ engagement, participation, and learning outcomes. Furthermore, the integration of Islamic values within the learning process contributes to the formation of students’ character. However, several challenges remain, including limited access to professional development, administrative workload, and uneven distribution of training opportunities. The study concludes that strengthening pedagogical competence is essential for improving the quality of learning in Islamic Elementary Schools. Therefore, continuous professional development, institutional support, and effective educational policies are required to ensure sustainable improvement in teaching practices.